Is Small Fiber Neuropathy Induced by Gadolinium-Based Contrast Agents?. Issue 8 (August 2020) - Radbruch, Alexander; Richter, Henning; Bücker, Patrick; Berlandi, Johannes; Schänzer, Anne; Deike-Hofmann, Katerina; Kleinschnitz, Christoph; Schlemmer, Heinz-Peter; Forsting, Michael; Paulus, Werner; Martin, Louise F.; van Thriel, Christoph; et al.
Abstract : Objectives: In recent years, complaints of patients about burning pain in arms and legs after the injection of gadolinium-based contrast agents (GBCAs) have been reported. In the current study, we investigated changes of small fibers in the epidermis as a potential cause of the patient complaints in a mouse model. Methods: Six groups of 8 mice were intravenously injected with either a macrocyclic GBCA (gadoteridol, gadoterate meglumine, gadobutrol), a linear GBCA (gadodiamide or gadobenate dimeglumine) (1 mmol/kg body weight), or saline (NaCl 0.9%). Four weeks after injection, animals were euthanized, and footpads were assessed using immunofluorescence staining. Intraepidermal nerve fiber density (IENFD) was calculated, and the median number of terminal axonal swellings (TASs) per IENFD was determined. Results: Nonparametric Wilcoxon signed-rank test revealed significantly lower IENFDs for all GBCAs compared with the control group ( P < 0.0001) with the linear GBCAs showing significantly lower IENFDs than the macrocyclic GBCAs ( P < 0.0001). The linear GBCAs presented significantly more TAS per IENFD than the control group ( P < 0.0001), whereas no significant increase of TAS per IENFD compared with the control group was found for macrocyclic GBCAs ( P < 0.237). Interpretation: It is unclear whether or at what dosage the decrease of IENFDs and the increase of TAS per IENFD found in the current animal model will appear in humans and if it translates into clinical symptoms. However, given the highly significant findings of the current study, more research in this field is required.